Transforming growth factor-β drives the transendothelial migration of hepatocellular carcinoma cells - Koudelkova, Petra; Costina, Victor; Dooley, Steven; Findeisen, Peter (International journal of molecular sciences, 2017)
The entry of malignant hepatocytes into blood vessels is a key step in the dissemination and metastasis of hepatocellular carcinoma (HCC). The identification of molecular mechanisms involved in the transmigration of malignant hepatocytes through the endothelial barrier is of high relevance for therapeutic intervention and metastasis prevention. In this study, we employed a model of hepatocellular transmigration that mimics vascular invasion using hepatic sinusoidal endothelial cells and malignant hepatocytes evincing a mesenchymal-like, invasive phenotype by transforming growth factor (TGF)-β. Labelling of respective cell populations with various stable isotopes and subsequent mass spectrometry analyses allowed the “real-time” detection of molecular changes in both transmigrating hepatocytes and endothelial cells. Interestingly, the proteome profiling revealed 36 and 559 regulated proteins in hepatocytes and endothelial cells, respectively, indicating significant changes during active transmigration that mostly depends on cell-cell interaction rather than on TGF-β alone. Importantly, matching these in vitro findings with HCC patient data revealed a panel of common molecular alterations including peroxiredoxin-3, epoxide hydrolase, transgelin-2 and collectin 12 that are clinically relevant for the patient’s survival. We conclude that hepatocellular plasticity induced by TGF-β is crucially involved in blood vessel invasion of HCC cells.